Relationship of maximal isometric torque produced in flexors and extensors rate to technique by judo athletes - Sterkowicz, S.; Lech, G.; Sterkowicz-Przybycien, K.; Chwala, W.; Ambrozy, T.; Palka, T. (Acta of Bioengineering and Biomechanics, 2018)
Purpose: Development of strength is one of essential elements of motor preparation of judo athletes. The aim this study was to examine the influence of body composition and the joint torques on successful performance of various judo techniques. Methods: Twentyfive judo athletes participated in 175 judo bouts, which were video-recorded during the All-Polish competitions. Biomechanical classification of technical actions was used. The age and athletic experience of the subjects were 18 and 8.8 years, respectively. Their body height was 179.4 cm (Martin¡¦s type anthropometer) and body mass was 80.3 kg (Sartorius F 1505 ¡V DZA scales). Percentage of fat (10.6%) was estimated using skinfold result measurements. BMI (24.9 kg"ªm¡V2), fat-free mass index (21.9 kg"ªm¡V2) and fat mass index (3.0 kg"ªm¡V2) were calculated. Maximum torques measured under static conditions were evaluated 2¡V3 days after the tournament. Descriptive statistics and ANOVA were conducted ( p "T 0.05). Results: Balancing of maximum torques in the muscles of the pelvic and illiac regions caused more frequent performance of physical lever-type throwing techniques, compared to couple of force-type throwing techniques. A negative correlation was found between body fat and value of force recorded for knee flexors and between the frequency of using techniques during groundwork and torques measured in hip extensors. High correlation of fat-free mass index and relative elbow flexor torque was found. Conclusions: The relationship between body composition and frequency of techniques used in a tournament, and joint torques developed by athletes were found.